PENGARUH LATIHAN ZIG ZAG RUN TERHADAP KELINCAHAN ATLET PENCAK SILAT TAPAK SUCI LEBONG - Nusardi Ahmad (Journal Physical Education, Health and Recreation, 2018)
Based on the observation in the field it shows that still lack of agility ability of athlete pencak silat tapak suci Lebong. This study aims to explain the effect of zig-zag run training on improving the agility ability of athlete pencak silat tapak suci Lebong. This research method is quasi-experimental with the population of this study a number of 17 athletes and samples taken by using the total sampling technique so that obtained a sample of 17 athletes. The test used is the Shuttle Run, which aims to determine the ability of agility. Data analysis technique used is t-test. The result of data analysis shows that zig zag run training method can increase agility of athlete pencak silat tapak suci Lebong (tcount (8,492)> ttable (2,110).